Mathematics

Question

g(x) = -4x+4
h(x)= x³+4x²
find g(x)•h(x)

1 Answer

  • Answer:

    4x^4-12x^3+16x^2

    Step-by-step explanation:

    (-4x+4)(x^3+4x^2)

    a      b    c      d

    using foil method multiply

    term a by term c and d

    -4x * x^3= -4x^4

    -4x * 4x^2= -16x^3

    *dont forget to add the exponents, when x is by itself you it always has an imaginary 1

    then multiply term b by term c and d

    4 * x^3= 4x^3

    4 * 4x^2= 16x^2

    line up all of your answers from biggest exponent to smallest

    -4x^4-16x^3+4x^3+16x^2

    we can combine like terms with -16x^3 and 4x^3 becaus ethey have the same exponent value

    4x^4-12x^3+16x^2

NEWS TODAY

You May Be Interested